A Validated LC-MS/MS Method for the Estimation of Bortezomib and Bortezomib D3 (IS) in Human Plasma with Protein Precipitation and SPE Filter Cartridges - Bhetanabotla Chandramowli, Bigala B. Rajkamal (Journal of Applied Pharmaceutical Science, 2017)
A simple, rapid, specific and precise liquid chromatography-tandem mass spectrophotometric (LC–MS/MS) validated method was developed for quantification of Bortezomib in human plasma. Bortezomib D3 was used as internal standard, added to plasma sample prior to extraction using 0.1% formic acid in acetonitrile as a precipitating agent. The interferences due to protein denaturation were removed using captiva SPE filter cartridge of 0.45µm. Chromatographic separation was achieved on ACE 5CN column (150mmx4.6mm) with acteonitrile: 10 mM ammonium formate buffer (75:25 v/v) as an isocratic mobile phase with a flow rate of 1 ml/min. the LC eluent was split, and approximately 0.1ml/min was introduced in to Tandem mass spectrometer using turbo Ion Spray interface at 325°C. Quantitation was performed by transition of 367.3 → 226.3 (m/z) for Bortezomib and 370.3 → 229.2(m/z) for Bortezomib D3. The concentrations of ten working standards showed linearity between 2 to 1000 ng/ml (r2 ≥ 0.998). Chromatographic separation was achieved within 3.5 min. The average extraction recoveries of three quality control concentrations were 82.71% for Bortezomib and were within the acceptance limits. The coefficient of variation was ≤15% for intra- and inter-batch assays. The assay is suitable for pharmacokinetic study samples as demonstrated by its specificity, precision, accuracy, recovery, and stability characteristics.
Keywords: Chlorella sp., Synechocystis sp., nitrogen, phosphorus, wastewater.